COMPARISON OF PHOTOMETRIC CYANMETHEMOGLOBIN AND AUTOMATED METHODS FOR HEMOGLOBIN ESTIMATION - Azim, Waqar; Parveen, Shahida; Parveen, Saadat (Journal of Ayub Medical College Abbottabad, 2002)
Background: Hemoglobin estimation is the most frequent laboratory investigation requested. Different methods include acid haematin, photometric cyanmethemoglobin estimation and automated estimation with the help of counters. Aims and objectives of the current study were to compare photometric cyanmethemoglobin method with hemoglobin estimation by Medonic automated counter. Methods: One hundred and ten adult cases were included through convenience sampling. Samples with hemolysis were excluded from the study. Blood was drawn in CP bottles. Sample was thoroughly mixed and hemoglobin estimation was done by Medonic counter as well by photometer 4010. Commercial controls were run with each batch. Results: By manual methods, results revealed mean 0.85% increase compared to automated counter. Commercial control results showed 2.3% and 2.7% coefficient of variation by Medonic counter and photometer 4010 respectively. Conclusions: It was concluded that both methods are accurate and precise, with reference range 2.61% more in manual method. It is recommended that with small samples and with parameters like hemoglobin or hemoglobin with erythrocyte sedimentation rate, manual method is cost effective and feasible. However with multiple parameters like absolute values and with very large batches, like in tertiary laboratory, automated method is time effective and feasible, provided the laboratory can bear the cost. Key Words: Hemoglobin estimation, Cell counter, Cyanmethemoglobin.